Metastatic Cutaneous Melanoma: A Rare Entity with a Unique Presentation - Pradhan, Manish; Rai, Deepa; Bhandari, Rashmi (Journal of Nobel Medical College, 2019)
The occurrence of cutaneous infiltration by malignancies has been accounted to 0.7 %- 9 % of patients suffering with malignant neoplasm and are generally thought to be a late consequence of most neoplasms.And, the prevalence of malignant melanoma as a primary tumor in one published study was 59 out of 381 patients. We herein report an unusual case of a patient who presented with multiple nodules of varying sizes over the body, which later revealed to be malignant melanoma; both on cytopathology and histopathology examination. As this is a rare, unusual condition in our setting, frequent and timely case reporting is to be done that will ensure the better management and outcome of the disease